Race categorization in noise. (July 2022) - de Lissa, Peter; Watanabe, Katsumi; Gu, Li; Ishii, Tatsunori; Nakamura, Koyo; Kimura, Taiki; Sagasaki, Amane; Caldara, Roberto
People are typically faster to categorize the race of a face if it belongs to a race different from their own. This Other Race Categorization Advantage (ORCA) is thought to reflect an enhanced sensitivity to the visual race signals of other race faces, leading to faster response times. The current study investigated this sensitivity in a cross-cultural sample of Swiss and Japanese observers with a race categorization task using faces that had been parametrically degraded of visual structure, with normalized luminance and contrast. While Swiss observers exhibited an increasingly strong ORCA in both reaction time and accuracy as the face images were visually degraded up to 20% structural coherence, the Japanese observers manifested this pattern most distinctly when the faces were fully structurally-intact. Critically, for both observer groups, there was a clear accuracy effect at the 20% structural coherence level, indicating that the enhanced sensitivity to other race visual signals persists in significantly degraded stimuli. These results suggest that different cultural groups may rely on and extract distinct types of visual race signals during categorization, which may depend on the available visual information. Nevertheless, heavily degraded stimuli specifically favor the perception of other race faces, indicating that the visual system is tuned by experience and is sensitive to the detection of unfamiliar signals.